Strength properties of sandy soil-cement admixtures - António Viana da Fonseca (2009)
Soil stabilization with cement is a good solution for the construction of subgrades for roadway and railway lines, especially under the platforms and mostly in transition zones between embankments and rigid structures, where the mechanical properties of supporting soils are very influential. These solutions are especially attractive in line works where other ground improvement techniques are extensive and, therefore, very expensive. On the other hand, the economic and environmental costs of such works should be optimized with good balances between excavation and embankment volumes. For this purpose, the improvement of locally available soils can bring great advantages, avoiding a great amount in borrowing appropriate material, as well as the need of disposing huge volumes in deposits. This paper focus on the characteristics of two soils, Osorio sand and Botucatu residual sandstone, which can be converted to well acceptable materials for this purpose, if stabilized with cement. The study of soil stabilization with cement relies on the quantification of the influence of percentage of cement and porosity adopted in the admixing process for different state and stress conditions. This influence will be evaluated from the analysis of unconfined compression strength (UCS or q u ) test results. This experimental framework will enable a good definition of mechanical parameters used in design of foundations and subgrades of railways platforms and for their execution quality control. (c) 2009 Springer Science+Business Media B.V.